The hardware and software complex for electromechanical equipment diagnostic - O. I. Gordeev; V. A. Zakharenko (Омский научный вестник)
The results of the development of the hardware and software complex for electromechanical equipment diagnostic by electrical power consumption parameters are presented. The connection of the prototype of the above-mentioned complex to the laboratory stand for vibration diagnostics of electromechanical equipment and the obtained possibilities for experimental research are described. The obtained experimental graphs of changes in the values of the main electrical power consumption parameters of the electric motor over time at different levels of load on the shaft of the stand are shown.